Non-Fee Based Interlibrary Loans: A Game-Changer in Israel. Issue 1 (13th May 2021) - Porat, Lynne; Nissan-Shalem, Orly; Perry, Shlomit
Abstract: A milestone occurred in Israeli Interlibrary loans when the Directors' Forum of the University Heads' Committee approved funding for a non-fee based ILL pilot in the eight universities, in an attempt to address the financial difficulties faced by humanities & social sciences students and researchers. The article reviews the literature on the ethics of fee charging, non-fee based ILL ventures, the financial burden on MA & PhD students, increased patron use and satisfaction, the costs and complications of fee charging and invoicing, and the global decline in ILL. It describes ILL services in 22 Israeli university libraries before and after implementation of a non-fee based pilot, and outlines the processes that led to the launching of the project. The purpose of the article is to present a model of project management, from its inception until its establishment as a permanent arrangement, and to show how the removal of fees was a game-changer, reviving Israeli ILL.